Kualiti Dalam Proses Pembangunan Sistem : Satu Dimensi Baru Kepada Kitar Hayat Pembangunan Sistem - Jamal, Othman (2000)
Failures in system implementation are nightmare for each developer. Enforcement of quality in the process of system development is able to produce good quality of systems. The main discussion of this research is to identify list of factors that influence in producing high quality of systems. Research has been done on the successful system, Human Resource Information System (HRIS) which has been developed as joint venture effort between Pusat Sistem Maklumat Bersepadu (PSMB) from Mara University of Technology and Far East Company (FEC Consultant Company). Several interviews have been handled with the head of developer and staff to know the secrets of success. Part of this research, I can conclude that, the involvement of knowledgeable users, starts from early until final stage of system development life cycle is one of the opportunities to success in the system development project. To confirm the effectiveness of user involvement and other groups of people, JAD will be the most suitable method. To produce good quality of system documentation, SSADM has been suggested as the most suitable methods, which always enforce on quality aspects. Prototyping becomes the subset of SSADM during system development process. SSADM, JAD and Prototyping are suitable if these three methodologies are hybrid together at analysis and design phases for the new model of System Development Life Cycle. The old System Development Life Cycle should be changed, so that the new image of SDLC has been embedded with formal methodologies that are focusing on quality aspects. From this study, all developers will realize about the usage of formal methodologies are able to produce high quality of systems.